The Development of Statistics E-Modul Using Flipbook on Junior High School - Anisa, Lia Nur; Yahya, Lailany; Kobandaha, Putri Ekawaty (IKIP Siliwangi, 2025)
Conventional learning methods tend to be monotonous, often making junior high school students less interested and difficult to understand the material, especially in statistics. Therefore, it is necessary to develop more interactive and interesting teaching materials to increase students' interest in learning and understanding. This research aims to develop of statistics e-modul valid and practical teaching using the flipbook on junior high school. This study is classified as Research & Development using Thiagarajan's 4D model. The 4D stages of Thiagarajan include Define, Design, Develop, and Disseminate. The data collected using the instruments employed in this study include a validation questionnaire consisting of subject matter experts and media experts, a readability test questionnaire, and student response questionnaires, as well as teacher response questionnaires used to measure the practicality of the developed e-module. The results of the the development of e-modul using the flipbook application falls under the criteria of validity and practicality. The level of validity can be seen from the validity scores of 74% for content validation and 78% for media validation, which fall within the valid category, as well as practicality scores were obtained from the student response questionnaire with a score of 85% and the teacher response questionnaire with a score of 98%. It can be concluded that the development of e-modules using the flipbook application for statistics material for eighth grade, as produced by this research, is valid and practical, and therefore considered suitable for use in learning.